Heterotopic peritoneal echinococcosis of splenic origin in children - Castiglioni, Juan C; Belloso García, Rogelio (Cirugía del Uruguay, 1973)
Description of a case of strangled diaphragmatic hernia of Bochdalek's hiatus, in an adult which evolved satisfactorily, This is completed by a review of world literature on the subject. It is interesting to note the low incidence of this disease in adults. Finally the author goes ever its ethiology, clínica! aspects an:I treatment.